Yudhiṣṭhiravijayam - Vāsudeva,Śokkanātha,Rameśa, Y. S. (Rāṣṭriyasaṃskṛtasaṃsthānam, 2007)
Based on Mahābhārata; includes Sanskrit commentary by Śokkanātha, 17th century
Epic poem. - Includes index. - Includes bibliographical references (p. [xxxix]-xlii). - Sanskrit in Devanagari-Schr
Keywords: Kommentar; Epic poetry; Sanskrit